PENGARUH LIVE STREAMING, FLASH SALE DAN CASH ON DELIVERY TERHADAP KEPUTUSAN PEMBELIAN MAHASISWA - Selvi Amalia Nur Aida; Jayanti Mandasarai (Neraca: Jurnal Ekonomi, Manajemen dan Akuntansi, 2025)
This study aims to analyze the influence of live streaming features, flash sale promotions, and the Cash On Delivery (COD) payment method on the purchasing decisions of students from the Faculty of Economics and Business at Universitas Teknologi Sumbawa on the Shopee e-commerce platform. This research employs a quantitative approach with a causal research design. The sample consists of 100 students selected using purposive sampling techniques. Data were collected using questionnaires with a four-point Likert scale and analyzed using multiple linear regression analysis. The results indicate that live streaming, flash sale, and COD each have a partial influence on purchasing decisions. Simultaneously, these three variables also have a significant influence on students' purchasing decisions. This research contributes to understanding young consumers' behavior in the digital era